Desarrollo afectivo - social en los niños y niñas en el nivel de educación Inicial - Saldafta Ortiz, Karla Llliana (2010)
Children from an early age tend to relate to the family system; observing and experimenting customs that develop in the family, for the game identified; with all the features and cultural events that take place in this environment. The family system is an institution with a hidden curriculum where a wealth of information is contained; where family lifestyles from one generation to another is transmitted; is a wealth of rich family experiences developed, which are shown in the training of children as an infant; mostly in the evaluative components that must be stamped on attitudinal training, good citizen for life. Affection, is the gift that is perceived from the beginning the conception of man by our mother; It is the first step in the development of the level of socialization of children in childhood and to reach this process, we need to develop in them skills such as expressive, affection, affection, to be affable, warm, loving. With these virtues developed and made manifest, we will have children with high esteem and sociable. In this monograph it consists of four chapters. The first chapter deals with content relating to conceptualization, characterization, development of affective skills and affective processes. The second chapter deals with the emotional theories, types and affective disorders. In the third chapter, is very important to develop content and emotional development of preschoolers; and emotional development - emotional and affective - social in children. The fourth chapter will address issues such as the role of teachers and parents in the emotional training; and the development of emotional and social skills of children in the Early Childhood Education Level